Ethanol Extract of Sesamum indicum Linn. Inhibits FcεRI-Mediated Allergic Reaction via Regulation of Lyn/Syk and Fyn Signaling Pathways in Rat Basophilic Leukemic RBL-2H3 Mast Cells - Do, Hyun Ju; Oh, Tae Woo; Park, Kwang-Il (Mediators of Inflammation, 2019)
This study is aimed at determining whether Sesamum indicum Linn. beneficially influences FcεRI-mediated allergic reactions in RBL-2H3 mast cells; it is also aimed at further investigating Lyn/Fyn and Syk signaling pathways. To examine the antiallergic effect of Sesamum indicum Linn. extract (SIE), we treated antigen/immunoglobulin E- (IgE-) sensitized mast cells with extracts of various concentrations. We examined the degranulation release and concentrations of inflammatory mediators. Additionally, the expressions of genes involved in the FcεRI and arachidonate signaling pathways were examined. SIE inhibited the degranulation and secretion of inflammatory mediators in antigen/IgE-sensitized mast cells. SIE reduced the expressions of FcεRI signaling-related genes, such as Syk, Lyn, and Fyn, and the phosphorylation of extracellular signal-regulated kinase in antigen/IgE-sensitized mast cells. Additionally, in late allergic responses, SIE reduced PGD2 release and COX-2 and cPLA2 phosphorylation expression in FcεRI-mediated mast cell activation. Lastly, 250–500 mg/kg SIE significantly attenuated the Ag/IgE-induced passive cutaneous anaphylaxis (PCA) reaction in mice. The potent effect of SIE on RBL-2H3 mast cell activation indicates that the extract could potentially be used as a novel inhibitor against allergic reactions.